Designing high dielectric breakdown strategy for high-temperature capacitive energy storage and filtering performance via carrier trap mechanism - Qingdan Wang; Ting Wang; Liming Chen; Qilinjia Mi; Pinrong An; Jianxiang Ding; Xiangong Den; Yifan Tang; Xihong Hao; Ruzhong Zuo (Journal of Advanced Ceramics)
Antiferroelectric (AFE) ceramic materials with excellent temperature stability are critical for meeting ever-increasing demands for practical energy storage applications. However, how to remain high dielectric breakdown strategy at high temperature, at the same time to keep energy storage density (Wrec) with high energy storage efficiency (η) is still a major challenge. In this work, polyurethane–Cu (PU–Cu) was introduced into a (Pb0.64Tm0.04La0.2)(Zr0.55Sn0.44Ti0.01) (PTL2ZST) AFE thick film to enhance the energy storage performance at high temperatures. PTL2ZST dispersed in PU–Cu because PU–Cu functions by introducing carrier traps, reducing conduction and leakage currents at high temperatures. As a result, at a working temperature of 140 °C, its Wrec and η remain within the range of ±5% compared with those of pure PTL2ZST (Wrec decreases by 21.7%, η increases by 9.4% at 100 °C). Furthermore, ultrahigh Wrec of 17.01 J/cm3 with η of 80.31% in PTL2ZST–90% PU–Cu thick films at 2500 kV/cm at room temperature (RT) was obtained. Moreover, this study has outstanding filtering performance because the high degree of insulation caused by carrier traps weakens the charge carrier transport. In the rectifier circuit, the PTL2ZST–90% PU–Cu films can filter off 90% of the clutter. This study provides a feasible method to produce high-performance dielectric materials because of their high energy storage performance and heat resistance, which also broadens the field of filter application.